Perbedaan Pengaruh Pendidikan Kesehatan TentangKaries Gigi Melalui Media Buku Cerita BergambarDan Leaflet Terhadap Pengetahuan, Sikap, DanPerilaku Anak Sekolah Dasar DiKabupaten Malang - Jannah, Zuhrotul; , H. Heru Subaris Kasjono, S.KM., M.Kes; , Yuli Kusumawati, S.KM., M.Kes (Epid) (2016)
According to WHO, increased prevalence of dental caries in 12 years old group, which amounts to 13,7% in 2007(28,9%) to 2013(42,6%). The media that used in this health education are picture story book and leaflet. East Java Province is one of three provinces that have increased oral and dental problems highest in Indonesia. The aim of this research is to know the differenciate influence of health education about dental caries by using picture story book and laflet of knowledge, attitude, and behaviour of elementary school in Malang regency. The research metohod is used Quasy Experiment. The plan of this research is used Pre-test and Post-test design. The population of this research are all of the students 3th class and 4th class in Elementary School Kemiri 1 dan Elementary School Tegalsari 1, that are 97 students. The selection of sample by Proportionale Stratifed Random Sampling as many as 78 students. The result of this research show that there is increase of knowledge (p=0,0001), the attitude (p=0,0001), the habitual of teeth brush (p=0,0001), and the step of teeth brush correctly (p=0,0001) of the group picture story and leaflet. The result of Mann Whitney show that there is significant difference between picture story book and leaflet of knowledge (p=0,037), the attitude (p=0,0001), and the step of teeth brush correctly (p=0,033). There is not significant difference of the habitual of teeth brush (p=0,121).